2003
DOI: 10.1046/j.1365-2400.2003.00332.x
|View full text |Cite
|
Sign up to set email alerts
|

Low allozyme variation in snapper, Pagrus auratus, in Victoria, Australia

Abstract: The population genetic structure of snapper, Pagrus auratus (Bloch and Schneider), in Victoria was investigated using six polymorphic allozyme loci. Fish were sampled from four sites in Victoria and single locations in South Australia, Western Australia and New Zealand. Although there were distinct genetic differences between the snapper populations from each of the Australian states and New Zealand, only minor and largely insignificant differences were detected among Victorian populations. The results are con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 9 publications
2
8
0
Order By: Relevance
“…Further evidence suggesting the existence of separate stocks on the south and east coasts of Australia has come from growth rate studies and tagging experiments (Sanders and Powell, 1979;Francis and Winstanley, 1989) which have largely been confined to South Australian and Victorian waters. A recent study by Meggs et al (2003) while noting distinct genetic differences between snapper populations in southern Australian state offshore waters (South Australia and Victoria) and New Zealand found only insignificant differences among Victorian populations.…”
Section: Introductionmentioning
confidence: 93%
“…Further evidence suggesting the existence of separate stocks on the south and east coasts of Australia has come from growth rate studies and tagging experiments (Sanders and Powell, 1979;Francis and Winstanley, 1989) which have largely been confined to South Australian and Victorian waters. A recent study by Meggs et al (2003) while noting distinct genetic differences between snapper populations in southern Australian state offshore waters (South Australia and Victoria) and New Zealand found only insignificant differences among Victorian populations.…”
Section: Introductionmentioning
confidence: 93%
“…Generally, dispersal limitations appear greater in passive dispersers, such as species with planktonic larvae, compared with species with more mobile adult forms (Ward and Elliot ; Meggs et al. ; Ayre et al. ; Shaddick et al.…”
Section: Introductionmentioning
confidence: 99%
“…For example, there is limited genetic differentiation between estuarine populations of black bream, Acanthopagrus butcheri, in eastern Australia (F ST = 0.004; Farrington et al 2000), whereas there is considerable genetic heterogeneity among estuarine populations of this species in Western Australia (F ST = 0.166; Chaplin et al 1998). Similarly, there is low genetic differentiation among snapper from embayments in Victoria (Meggs et al 2003), whereas significant differentiation has been observed among populations from Western Australia (Johnson et al 1986). The flood plumes of many rivers on the east coast ofAustralia are known to merge during flood pulse events, whereas many estuaries in Western Australia have low and/or highly seasonal discharge and become closed to the ocean for extended periods of time (Hodgkin and Lenanton 1981).…”
Section: Discussionmentioning
confidence: 99%
“…In Australia there is evidence of subdivision in the catadromous Australian bass (Macquaria novemaculeata; Chenoweth and Hughes 1997;Jerry 1997) and barramundi (Lates calcarifer; Shaklee and Salini 1983;Salini and Shaklee 1988;Shaklee et al 1993;Keenan 1994), the estuarine-spawning black bream (Acanthopagrus butcheri; Chaplin et al 1998;Farrington et al 2000), and several fish species that spawn in marine and estuarine or enclosed embayment environments including cobbler (Cnidoglanis macrocephalus; Ayvazian et al 1994), snapper (Pagrus auratus;MacDonald 1980;Johnson et al 1986;Meggs et al 2003), two species of hardyhead (Craterocephalus capreoli and Leptatherina presbyteroides; Watts 1991;Johnson et al 1994) and gobbleguts (Apogon rueppellii; Watts 1991). The ecological importance of this genetic subdivision is that some estuarine populations may be isolated and self-sustaining, with important implications for fisheries management and conservation (Johnson et al 1986;Richardson et al 1986;Ayvazian et al 1994;Chaplin et al 1998).…”
Section: Introductionmentioning
confidence: 99%